Home Visit Learning Assistance as a Solution to Learning Problems During the Covid-19 Pandemic - Sagala, Rakhmat Wahyudin; Nasution, Khalifahtusya’diah (PT. Berlian Pustaka Indonesia, 2023)
This community service aims to obtain information regarding obstacles during the teaching and learning process in the network during the Covid-19 pandemic. This activity also aimed to reveal the effectiveness of study assistance by Community Service Teams of Universitas Muhammadiyah Sumatera Utara. The study in this activity uses the action research method to obtain information about the constraints and consequences of the Covid-19 pandemic for students and parents during the learning process with courage. The objects of this community service activity are school children who are supported in their natural learning process. Obstacles that occur in the subject of community service activities, namely mastery over the use of technology, which tends to be low due to the high cost of using or purchasing internet packages, besides that the subject has difficulty interacting directly with teachers and colleagues plus the assignments from the teacher are so many that it confuses students. The study results show that home visit learning can help students in their learning activities. Learning assistance is carried out openly by the research team. Community service activities were carried out in Desa Saentis, Percut Sei Tuan, Sumatra Utara